Overview Bell’s Palsy - Putu Lina Yes, Ni (Jurnal KESANS : Kesehatan dan Sains, 2024)
Bell's palsy is a condition that causes temporary paralysis of the muscles on one side of the face. It is caused by facial nerve inflammation that controls the facial muscles. The exact cause of Bell's palsy is unclear, but it is associated with viral infections such as herpes simplex, varicella-zoster, and Epstein-Barr. All genders and ages are affected with a higher risk in people with diabetes, hypertension, pregnant women, obesity, and people with upper respiratory tract infections. Potential pathogenesis includes factors related to facial nerve anatomy, viral infection, local ischemia and inflammation, cold exposure, and autoimmune response. This review aims to provide a focused understanding of the anatomy, clinical features, etiology, diagnosis, and therapy of Bell's Palsy